Design of a Real-Time Gas-Exchange Measurement System for Crop Stands in Environmental Scenarios - Hans-Peter Kläring; Oliver Körner (Agronomy, 2020)
In contrast to conducting measurements on single plants, canopy gas exchange monitored continuously and for large batches of plants can give high-value data for crop physiological models. To this end, a system including eight airtight greenhouse cabins with a ground area of 28.8 m2 and a volume of 107.8 m3 each was designed for measuring the CO2 and H2O gas exchange of crop stands following the general principle of semi-open chambers. The measuring facility consists of a set of mass flow meters allowing air exchange rates between 0.5 h−1 and 19 h−1 (i.e., m3 gas per m3 greenhouse air per hour) and CO2 supply rates up to 4 L min−1 (i.e., ca. 14.9 g m−2 greenhouse h−1) and sensors for measuring the concentrations of CO2 and H2O. There are four separated belowground troughs per cabin for the root environment that can be operated as individual gas exchange chambers measuring the belowground gas exchange for example root zone respiration. This paper outlines a demonstration of the possibilities and constraints for measuring crop gas exchange in combination with crop model validation for larger crop stands under various conditions and discusses them along with examples.